2013
DOI: 10.12989/amr.2013.2.2.111
|View full text |Cite
|
Sign up to set email alerts
|

A study of plastic plateau disappearance in stress-strain curve of annealed polypropylene films during stretching

Abstract: The changes of plastic plateau in the stress-strain curves of annealed polypropylene (PP) films during stretching under room temperature were followed and the corresponding melting properties and microstructure were characterized by differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). It was found that during stretching the plastic plateau disappeared progressively with the increase of drawing ratio. At the same time, the endotherm plateau in DSC curves also disappeared progressively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
2
12
1
Order By: Relevance
“…Figure 9 presents the DSC curves of samples at different stretching stages. With the increase of drawing ratio, the endotherm plateau formed during annealing disappears progressively, in agreement with the former results given in our previous articles [18,19]. As can be seen, from Sample A to Sample E, the DSC curves for PP-B and PP-G do not show much difference.…”
Section: Properties Of Precursor and Annealed Filmsupporting
confidence: 92%
“…Figure 9 presents the DSC curves of samples at different stretching stages. With the increase of drawing ratio, the endotherm plateau formed during annealing disappears progressively, in agreement with the former results given in our previous articles [18,19]. As can be seen, from Sample A to Sample E, the DSC curves for PP-B and PP-G do not show much difference.…”
Section: Properties Of Precursor and Annealed Filmsupporting
confidence: 92%
“…In our previous work, it was found that the DSC curves of annealed film showed an endotherm plateau before the main melting peak, similar to the DSC curves of the heat‐set microporous membrane in Fig. .…”
Section: Resultssupporting
confidence: 77%
“…As to the second stage—the annealing process—the annealing temperature, annealing time and tension level (percent extension) control the annealing effect . In our previous work we found that, during cold stretching, the low‐temperature endotherm plateau in the DSC curves and the plastic plateau in the stress–strain curves of annealed films disappeared progressively and their disappearance corresponded to the formation of an initial bridge structure connecting separated lamellae. Recently, we have found that, compared with that formed only through cold stretching, more connecting bridges were initiated during hot stretching .…”
Section: Introductionmentioning
confidence: 99%
“…In the works by Carreau group in the field of PP microporous membrane, the roomtemperature stretching ratio was set at 35-40 % [7][8][9][10][11] , based on the direct comparison of structure and properties of stretched microporous membrane. In our previous work [14][15][16] , to follow the changes induced by room-temperature stretching, the room-temperature stretched films were heat-set at 145 °C for 10 minutes to decrease their shrinkage. This is since the annealed films show higher elastic recovery and the stretched film by only room-temperature stretching will recover to its unstretched state after the stretching stress is relieved.…”
Section: Introductionmentioning
confidence: 99%